(untitled) (American Journal of Research in Humanities and Social Sciences, 2023)
The family tests the customs of the people, society, and life. He keeps the good ones in his bosom and passes them on to future generations. The family educates its children and instills them with universal values, giving them the initial social direction. By integrating their children into the larger flow of society, the family also influences the direction, economy, culture, and education of society. That is why the family has been considered a sacred fortress in the East since ancient times.